New and emerging treatments of Guillain–Barré syndrome. (August 2014) - Lehmann, Helmar C; Zhang, Gang; Sheikh, Kazim A
<x xml:space="preserve">Abstract</x> Introduction: Guillain-Barré syndrome (GBS) is an acute inflammatory monophasic peripheral neuropathy of autoimmune origin. Although there are effective immunomodulatory treatments available for GBS, a substantial number of patients are left with residual neurological deficits. Nowadays, it is accepted that autoantibodies against gangliosides are pathogenic effectors in subtypes of GBS. It has been demonstrated that these autoantibodies can not only induce damage to intact nerve fibers but also inhibit axon regeneration after nerve injury, which might potentially account for the slow/poor recovery and prognosis in some GBS patients. Areas covered: Recent insights into the pathogenesis of GBS led to the recognition of promising targets for future development of novel therapies. This review discusses potentially new and emerging treatments that stemmed from preclinical studies. These emerging treatments can be grouped into immunomodulatory/anti-inflammatory and neuroprotective categories including inhibition of complement activation, enhanced clearance of autoantibodies against gangliosides by blocking neonatal Fc receptor, modulation of Fc γ receptors-mediated inflammation by sialylated intravenous Ig (IVIg) or IVIg-mimics and strategies for neuroprotection/enhancing regeneration by erythropoietin. Expert opinion: New and emerging treatments offer promise to optimize therapy for GBS patients, especially those who are refractory to currently used treatment modalities in the short term and those who are at higher risk of developing permanent sequelae (neurological deficits) in the long run.